Twenty-Five Hours in a Day: On Job Flexibility and the Intrahousehold Allocation of Time and Money - Iris Kesternich; Frederic Vermeulen; Alexander Wintzéus (CESifo GmbH, 2024)
Flexible work schedules and telecommuting may help to improve the combination of work and family. This is arguably most important in households with (young) children. An open question is whether job flexibility can increase the well-being of the children, which depends, in part, on the time spent on child care by the parents. In couples, the allocation of time depends not only on the time and budget constraints these couples are faced with, but also on the (possibly diverging) preferences of mothers and fathers and their respective bargaining positions. To address this question, we propose a rich collective model describing the intrahousehold allocation of time and money, where children's well-being is treated as a domestically produced good. Job flexibility may influence this domestic production process as a production shifter, capturing that flexible jobs can ease constraints on child care time parents may encounter. We apply our model to a unique sample of Dutch couples with children and find that job flexibility significantly impacts the production of children's well-being. While the results indicate that more job flexibility for fathers may help parents to balance work and family, they imply that more job flexibility for mothers may not allow parents to achieve the same. The overall implications for children's well-being appear negative, albeit limited.
Keywords: D13; J12; J22; 330; household behaviour; labor supply; gender differences; amenities; job flexibility; child care